Perubahan Struktur Energi Jerman dan Implikasinya terhadap Hubungan Dengan Rusia; Studi Kasus Nord Stream 2 - Nurtyandini, Resqita Trisya; Argenti, Gili; Hakiem, Fadhlan Nur (Jurnal Intervensi Sosial dan Pembangunan, 2024)
This research explores the shifts in Germany's energy structure and their implications for relations with Russia through the case of Nord Stream 2. The research focuses on economic impact, energy security, and energy diplomacy. Using a descriptive qualitative approach, the analysis is based on secondary data from various sources such as energy reports and government policies. The findings reveal that Germany's reliance on Russian gas via Nord Stream 2 increases economic and energy security risks, including supply disruptions and gas price fluctuations. Germany’s efforts at energy diversification at the national and EU levels have not fully mitigated these risks. The study recommends more aggressive energy diversification strategies and greater investment in renewable energy to reduce long-term dependence and calls for a comprehensive energy policy that also considers international diplomacy to support sustainable global relations.Keywords: Germany, Russia, Natural Gas, Nord Stream 2, Energy Security